Clinical consequences of perinatal hypoxic-ischemic lesions of the central nervous system in infants born prematurely - Vareshniuk, Olena (Journal of Education, Health and Sport, 2018)
In the course of work, in order to study the leading risk factors for the unfavorable prognosis of development of impaired motor function in children born prematurely who underwent perinatal hypoxic-ischemic brain injury, a comprehensive examination of 79 children at an average age of 3.2 ± 1.3 years, who suffered from perinatal hypoxic-ischemic lesions of the central nervous system, and who were born prematurely, was conducted. As shown by the results of the survey, in 20.3% of the surveyed, it was found spastic cerebral palsy with severe motor disorders of the 4-5th levels according to the Gross Motor Function Classification System (GMFCS); 37.9% had spastic diplegia, 22.6% of which had motor disorders of the 3rd level by GMFCS, 15.3% had motor disorders of the 2nd level; 27.8% were diagnosed with hemiplegic form of cerebral palsy with the 1st level of motor disorders. 14.0% were diagnosed with acquired post-hemorrhagic hydrocephalus, 63.6% were operated on up to 6 months of age, they were implanted with liquor-bypass system and had motor disorders of the 1-2nd level; 27.3% of children were operated on after 6 months of life and had motor disorders of the 3rd level, and 9.1% were not operated on and had the 5th level of motor disorders. It has been established that the most important factors that form the difficult motor prognosis are gestational age of 27 - 30 weeks, peri-intraventricular hemorrhages of 2-4 degrees, periventricular leukomalacia of the 3rd degree, presence of signs of periventricular ischemia. Predictors of the formation of severe disorders of motor functions (inability to absorb walking, mastered only walking with auxiliary devices) in premature infants are pronounced ischemic brain injury, spastic form of cerebral palsy, operated on after 6 months of life, or generally non-operative acquired post-hemorrhagic hydrocephalus, gestational age 27 - 30 weeks, peri-intraventricular hemorrhage of 2-4 degrees, periventricular leukemalacia of the 3rd degree.